Excerpts from the author's works - Nedich, Jorge Emilio (Romano džaniben, 2021)
Czech translation of two short stories by J. E. Nedich (It was a very clever dog - El perro era tan inteligente que solo le faltaba hablar); and Childhood - Infancia) from the upcoming short story collection En cuentos de caravana (Stories from caravan). Introductory text includes biographical information compiled by the author himself and his selected bibliography.
Keywords: Literatura; Romani literature; Latin America